Faktor-Faktor Komunikasi Persuasif Dinas Pariwisata Dan Kebudayaan Provinsi DKI Jakarta Dalam Jakarta Museum On Social Media Competition - Elvio Tamara; Dini Safitri (Communications, 2019)
DKI Jakarta Tourism and Culture Office utilizes social media to invite millennial generations to love museums. This was done, because of the lack of interest of the young generation to visit Mueseum. In addition, the Office of Tourism and Culture (Disparbud) of DKI Jakarta Province makes the Jakarta Museum On Social Media Competition. The purpose of this study was to determine the Persuasive Communication Factors of DKI Jakarta Tourism and Culture Office in inviting millennial love museums through the Jakarta Museum On Social Media Competition. Research uses variable factors - persuasive communication, which has four dimensions, namely source credibility, environmental influences, messages, and continuity of understanding of a message. The approach in this study is a quantitative approach, with a type of descriptive research. The population and sample were 38 people, who were participants in the vlog category competition. The results of the study show that there are some things that are lacking in the factors of persuasive communication carried out by the Department of Tourism and Culture of DKI Jakarta Province. This can be seen in the lowest mean, namely the influence of the environment with time setting indicators and message content settings. Respondent Mayortias considered the DKI Jakarta Tourism and Culture Office to be less than optimal in utilizing the time in the Jakarta Museum On Social Media Competition, which resulted in a minimal number of participants.